Development of Cost Optimized Horizontal Gel Electrophoresis Running Unit for Developing Countries (Nepal) - Aryal, Sajesan; Hada, Aroj; Hamal, Sanjay; Prajapati, Abhishek; Timilsina, Paras Mani; Adhikari, Sandeep (Nepal Journal of Biotechnology, 2019)
The use of expensive lab techniques has left many high schools and even university students unacquainted with the basic experimental procedures and protocols in developing country including Nepal. Horizontal gel electrophoresis is one of the expensive protocols, which every student in the laboratory may not get an equal chance to access individually. However, this technique, being indispensable and inevitable in molecular biology principles, is of abounding importance for students to be familiar with. Thus, realizing its importance, we present an extremely simple and inexpensive design of gel-electrophoresis unit, which emulates electrophoresis analysis with the use of nichrome and aluminum wires as a substitute for platinum wires, together with daily used plastic materials. Because of these factors, the approximate cost of unit design is significantly reduced to an amount of 10 USD. The efficiency of the substitute wires was confirmed and it resulted in satisfactory data characterized by good resolution of the DNA fragments. The inexpensive nature, good results and simplicity of the device make it an ideal unit for teaching and learning in developing countries.